2013
DOI: 10.1128/jvi.00917-13
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Upregulates CD55 Expression on the Hepatocyte Surface and Promotes Association with Virus Particles

Abstract: CD55 limits excessive complement activation on the host cell surface by accelerating the decay of C3 convertases. In this study, we observed that hepatitis C virus (HCV) infection of hepatocytes or HCV core protein expression in transfected hepatocytes upregulated CD55 expression at the mRNA and protein levels. Further analysis suggested that the HCV core protein or fulllength (FL) genome enhanced CD55 promoter activity in a luciferase-based assay, which was further augmented in the presence of interleukin-6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Viral infection upregulated the expression of the regulatory proteins (Fig. 2, compare lane 1 vs lane 2; lane 5 vs lane 6), which was also observed with other viruses as part of virus-induced immune regulation (Mazumdar et al, 2013). Two forms of the CD46 and CD55 molecules were detected in infected cells and the lower molecular weight versions of both CD46 and CD55 forms were enriched in infected cells and purified viruses.…”
supporting
confidence: 67%
“…Viral infection upregulated the expression of the regulatory proteins (Fig. 2, compare lane 1 vs lane 2; lane 5 vs lane 6), which was also observed with other viruses as part of virus-induced immune regulation (Mazumdar et al, 2013). Two forms of the CD46 and CD55 molecules were detected in infected cells and the lower molecular weight versions of both CD46 and CD55 forms were enriched in infected cells and purified viruses.…”
supporting
confidence: 67%
“…c-Kit promoter activity is known to be upregulated by Sp1 (27). In previous studies, we and others have reported that HCV core enhances Sp1 promoter activity (28,29), which may be a mechanism by which c-Kit expression is enhanced in the presence of HCV.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that HCV core protein expression induces CD55 (15). Immortalized human hepatocytes (IHH) generated by stable transfection of HCV (genotype 1a) core genomic region into primary human hepatocytes (33) enhanced CD55 expression on cell surface.…”
Section: Resultsmentioning
confidence: 98%
“…In our previous study, we have shown that VSV G antibody induces complement dependent cytolysis (CDC) in VSV infected cells (15). Here, we used VSV infected BHK21 cells as a model to demonstrate the effect of sCD55 on CDC, as CD55 is not expressed on the cell surface of BHK21 cells (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation